#### Answer

$9$

#### Work Step by Step

$\lim _{x\rightarrow 2}\left( 3x^{2}-2x+1\right) =\left( 3\times 2^{2}-2\times 2+1\right) =12-4+1=9$

Published by
Pearson

ISBN 10:
0-32193-104-1

ISBN 13:
978-0-32193-104-7

$9$

$\lim _{x\rightarrow 2}\left( 3x^{2}-2x+1\right) =\left( 3\times 2^{2}-2\times 2+1\right) =12-4+1=9$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.